2006
DOI: 10.2353/ajpath.2006.050469
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RNA-Binding Protein Musashi in Hair Follicle Development and Hair Cycle Progression

Abstract: Epithelial stem cells reside in the hair follicle (HF) bulge region and possess the ability to differentiate into a variety of cutaneous epithelial cells. The evolutionarily conserved Musashi family of RNA-binding proteins is associated with maintenance and/or asymmetric cell division of neural progenitor cells, and a mammalian Musashi protein is expressed in various epithelial stem/progenitor cells, including gut, stomach, and mammary gland. Thus, we hypothesized that Musashi might be expressed in stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…It is highly expressed in neural stem cells and has been suggested to play an important role in the selfrenewing activity and survival of such immature cells [3][4][5][6][7]. The expression of Msi-1, a mammalian neural RNAbinding protein, is regulated concurrently with cell differentiation and growth [4][5][6][7][8][9]. Msi-1 is believed to have a critical function in posttranscriptional gene regulation, such as stabilization, splicing, and translational control of mRNA [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly expressed in neural stem cells and has been suggested to play an important role in the selfrenewing activity and survival of such immature cells [3][4][5][6][7]. The expression of Msi-1, a mammalian neural RNAbinding protein, is regulated concurrently with cell differentiation and growth [4][5][6][7][8][9]. Msi-1 is believed to have a critical function in posttranscriptional gene regulation, such as stabilization, splicing, and translational control of mRNA [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…12 Msi1 defines a population of multipotent stem cells in the brain, intestinal crypt cells, breast and hair follicles. [13][14][15][16][17][18][19][20] Msi1 has been determined to be highly expressed in several malignancies, such as glioblastoma Musashi1 (Msi1) is an evolutionarily conserved RNA-binding protein that has been implicated in processes like stem cell fate, nervous system development and tumorigenesis via its activities as a specific regulator of translation. While Msi1 is barely detected in normal adult tissue, it has been observed to be highly expressed in numerous tumor types (e.g., breast, colon, medulloblastoma, glioblastoma, et cetera).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biological studies revealed that in mouse Msi1 in these cells controls the Notch signaling pathway through translational reduction of the m-Numb protein, an inhibitor of the Notch pathway, and thereby maintains the stem/progenitor cell status (19). Interestingly, expression of Msi1 was also observed in many types of somatic stem cells in adult tissues, e.g., eye (20), intestine (21), stomach (22), mammary gland (23), and hair follicle (24). Furthermore, significant expression of the protein was observed in proliferative cell populations of tumor tissues (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%